Custom House, Trinidad. - (:unkn) unknown (Davidson-Todd. Ltd., 2011)
A picture of Custom House, Port of Spain. In this picture you can see boats docked and the train as it approaches custom house.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Railroad cars--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain